(untitled) (New Jersey, 2002)
The proceedings of the 4th Italy-Japan Symposium on Heavy Ion Physics cover the following fields of nuclear physics: heavy ion nuclear reactions; nuclei under extreme conditions; nuclear astrophysics; photon detectors and physics; technology of RI beams and experimental instrumentation; application of RI beams
Keywords: Heavy ions